Parent–child communication on sexual and reproductive health in border districts of Eastern Uganda - Kisaakye, Peter; Ndugga, Patricia; Kwagala, Elizabeth; Kayitale Mbonye, Martin; Ngabirano, Fred; Ojiambo Wandera, Stephen (Sex Education, 2022)
Parent-child communication concerning sexual and reproductive health (SRH) has significant potential to reduce children’s risky sexual behaviour. Despite these benefits, few parents communicate with their children about SRH issues in Uganda. Using multistage stratified sampling in a cross-sectional survey, we estimated the prevalence and investigated the factors that were associated with recent parent-child communication among 600 children (10- 17 years) in border districts of Uganda (Busia and Tororo). Results indicated that 61% of children reported to having received parentchild communication on SRH. Communication was more likely to happen among children living in urban areas (OR=4.88; 95% CI=1.79-13.33), boys (OR=1.84; 95% CI=1.13-3.00), those aged 15- 19 years (OR=2.59; 95% CI=1.51-4.46) and among children from households that owned a mobile phone (OR=2.11; 95% CI=1.05- 4.21) than their counterparts. Parent-child communication was also higher among children who were comfortable discussing SRH issues (OR=27.12; 95% CI=16.02-45.89) and children from Tororo district (OR=2.34; 95% CI=1.36-4.01). The findings provide a rich understanding of the factors associated with Parent-child communication in the border districts of Uganda. These results provide a basis for policy enactment or revision regarding the encouragement of parent-child communication about SRH in Uganda.
Keywords: Parent–child communication; sexual and reproductive health; Border districts